Analisis pengaruh ketebalan dan jenis Coating terhadap kekuatan Adhesi pada Pelat Baja SA 516 Gr 70 - Rachmad Syarifudin H; Wahyu Dwi K; Sigit N; Muhammad Syauqi (ARMATUR : Artikel Teknik Mesin & Manufaktur, 2026)
SA 516 Gr 70 carbon steel is often used in pressure vessels, requiring a coating system with good adhesive strength to prevent failure due to corrosion. This study analyzes the effect of coating type and thickness on the adhesive strength of SA 516 Gr 70 plates using the pull-off test method in accordance with ASTM D4541. The two coating systems tested were Interbond 2340 (UPC) and Interline 399, with variations in dry film thickness (DFT) of 75 µm, 125 µm, and 175 µm. Surface preparation was carried out through an abrasive blasting process with a cleanliness level of Sa 2½, accompanied by control of roughness profile, salt contamination, dust cleanliness, and control of application environmental conditions to maintain coating quality. Test results show that Interbond 2340 produces higher adhesion values than Interline 399 across all thickness variations, confirming the influence of coating type on coating adhesion performance. A maximum adhesion value of 17.09 MPa was obtained for Interbond 2340 with a thickness of 125 µm, indicating the optimal thickness for increasing the bond strength of the coating to the steel substrate. All specimens met the ASTM D4541 requirements, with Interbond 2340 at a thickness of 125 µm showing the most superior adhesion performance and can be used as a technical reference in selecting a coating system for pressure vessel applications.